Public Administration Reform over Time : Did Change Lead to a More Effective Integrity Management? - Demmke, Christoph (Faculty of Public Administration, University of Ljubljana, 2020)
The following discussion adds to the discourse regarding the relationship between public administration reform and ethics policies. In this theoretical paper, a narrative is employed that re-reads the old Weberian model as a model of ‘institutional integrity’, which is slowly replaced by a public management concept that focuses on individual integrity. Whereas the Weberian concept defined institutional integrity as a quality of institutions, more recent management concepts define institutional integrity as a quality of public officers within institutions. This also explains why the current focus of attention is ever more on individuals (as the main cause for unethical conduct) and the bad-person model of integrity. An alternative framing of this paper is about ‘institutional ethics’ over time. During the last decades, we are moving from an institutional, but mechanical and rigid Weberian model, to an individual, but more fluid New Public Management model. We are moving towards a version of institutional integrity that tries to use new behavioural mechanism to get back to some Weberian virtues, without its structures and technical focus. This novel ‘integrity management’ movement is really all about filling the gaps left by New Public Management doctrines. However, the reform of integrity management also develops into a specialised, sophisticated and professionalised ethics bureaucracy. Trends are towards ever more broader and stricter integrity requirements. Still, ethics policies are ineffective and shortcomings in implementing integrity policies are neglected.
Keywords: integrity management; bureaucracy; public management reform; behavioural policies; ethics; fi=Julkisjohtaminen|en=Public Management|